Apoptosis and eryptosis: similarities and differences - Tkachenko, Anton (Apoptosis, 2024)
Eryptosis is a regulated cell death (RCD) of mature erythrocytes initially described as a counterpart of apoptosis for enucleated cells. However, over the recent years, a growing number of studies have emphasized certain differences between both cell death modalities. In this review paper, we underline the hallmarks of eryptosis and apoptosis and highlight resemblances and dissimilarities between both RCDs. We summarize and critically discuss differences in the impact of caspase-3, Ca2+ signaling, ROS signaling pathways, opposing roles of casein kinase 1α, protein kinase C, Janus kinase 3, cyclin-dependent kinase 4, and AMP-activated protein kinase to highlight a certain degree of divergence between apoptosis and eryptosis. This review emphasizes the crucial importance of further studies that focus on deepening our knowledge of cell death machinery and identifying novel differences between cell death of nucleated and enucleated cells. This might provide evidence that erythrocytes can be defined as viable entities capable of programmed cell destruction. Additionally, the revealed cell type-specific patterns in cell death can facilitate the development of cell death-modulating therapeutic agents.
Keywords: buněčná smrt; Cell Death; Calcium; vápník; Reactive Oxygen Species; Phosphatidylserines; signální transdukce; Erythrocytes; Signal Transduction; eryptóza; fosfatidylseriny; Eryptosis; erytrocyty; apoptóza; reaktivní formy kyslíku; Apoptosis